Numbers don't lie 71 stories to help us understand the modern world - Smil, Vaclav 1943- (Penguin Books, 2021)
"Vaclav Smil's mission is to make facts matter. An environmental scientist, policy analyst, and a hugely prolific author, he is Bill Gates' go-to guy for making sense of our world. In Numbers Don't Lie, Smil answers questions such as: What's worse for the environment--your car or your phone? How much do the world's cows weigh (and what does it matter)? And what makes people happy?"--
Keywords: Globalisierung; Zivilisation; Energie; Demographie; Umwelt; Statistik; Civilization, Modern; Globalization; World politics; Technology and civilization; Human ecology; Statistics